Identity Exploration of Arabic Teachers: the Efforts to Become a Driving Teacher - Hamidah, Hamidah; Wahdah, Nurul; Mubarak, Mahfuz Rizqi; Syukriansyah, Ahmad (UIN Sunan Gunung Djati Bandung, 2023)
To realize the driving of teachers as planned by the government, it cannot be separated from various forms of professional competence that must be mastered as teachers’ identity. However, the identity, which is the qualification standard, is not evenly shared by Arabic language teachers, especially in several districts in the Kalimantan region. Therefore, this research aims to describe the identity of Arabic teachers as driving teacher resources in Arabic language learning to become driving teacher figures in the Kalimantan Region. This research uses a mixed method, combining qualitative and quantitative methods using a concurrent triangulation design. The research results show that the identity of Arabic teachers in Central Kalimantan is formed from their experiences so far, which require them to do more even though some do not have a non-Arabic language educational background. The emotional aspect of Arabic teachers who teach the Arabic language used in the Al-Quran and hadith fosters the teacher's enthusiasm to become a motivator, inspiration, and facilitator who always looks for solutions to problems in learning Arabic. Even though the teachers are located in the regions, this does not reduce the teachers' identity as teachers with pedagogical, social, personal, and professional competencies. Individuals who play the role of teachers always learn continuously throughout life and have the moral, emotional, and spiritual maturity to behave according to a code of ethics: planning, implementing, reflecting, and evaluating learning. This research recommends exploring the identity of Arabic teachers not only at the regional level but also at the national level.